Prevention of non-invasive ventilation injuries in preterm infants: a systematic review - João Emanuel Pereira Domingos; Ana Raquel Bezerra Saraiva Tavares; Vanusa Maria Gomes Napoleão Silva; Beatriz de Castro Magalhães; Guilhermi da Silva Maia; Edna Maria Camelo Chaves (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To identify scientific evidence regarding preventive care for pressure injuries related to the use of noninvasive ventilation in preterm newborns. Method: Systematic literature review, conducted in the databases PubMeb/Medline, EMBASE, Scopus, Web of Science, CINAHL-EBSCO, and LILACS, via the Virtual Health Library. Randomized controlled clinical trials were included, with no language restrictions and no time frame. Methodological quality was assessed using the Grading of Recommendations Assessment, Development and Evaluation system, and risk of bias was assessed using the Revised Cochrane risk-of-bias tool for randomized trials. Results: The search identified nine randomized clinical trials, published in English, between 2010 and 2021. Most studies were rated as having high quality of evidence. All performed random allocation and had low risk of bias. Conclusion: High-quality evidence recommends the adoption of systemic rotation between mask and nasal prongs, associated with the use of a hydrocolloid protective barrier, as a priority preventive intervention to reduce pressure injuries in preterm infants undergoing noninvasive ventilation. Integrated with daily inspection of skin integrity and adequate maintenance of humidification, this strategy promotes safe, effective, and high-quality care.